Удосконалення технології хлорування етилену - Шпарій, Микола Володимирович (Національний університет "Львівська політехніка", 2021)
В дисертаційному дослідженні розв’язана актуальна науково-практична задача: підвищення селективності процесу рідиннофазного прямого хлорування етилену до 1,2-дихлоретану шляхом модифікації промислового каталізатора на основі хлоридів заліза та натрію натрієвою сіллю перфорованої сульфокислоти. Уточнено механізм реакції прямого хлорування етилену і показано , що швидкість реакції залежить від концентрації каталізатора і промотора та їх комплексної сполуки [NаFeСІ4], а також перехідного комплексу з етиленом [Na[Fe(С2Н4Cl)4] ) , і проходить у дифузійній зоні, що передбачає можливість утворення комплексних сполук між каталізатором, промотором та етиленом механізмом реакції. Показано, що застосування в якості стабілізаторів каталітичного комплексу хлориду амонію не дає позитивного ефекту, а натрієва сіль перфторованої сульфокислоти веде не тільки до зростання вмісту йонів натрію в каталітичній системі і досягнення проектних їх значень, але й до зростання чистоти 1,2-дихлоретану та зменшення вмісту побічних продуктів, при цьому дисперсність каталітичної системи має другорядне значення. Встановлено, що модифікатор не тільки стабілізує каталітичний комплекс, але дозволяє скоротити час його приготування у два рази. Визначено оптимальну концентрацію стабілізатора. Визначено склад шламу, що засмічує газопровід від печі до парогенератора системи утилізації тепла при термічному знешкодженні кубових залишків виробництва вінілхлориду. Запропоновано принципи технології вилучення хлориду заліза - каталізатора прямого хлорування етилену - з технологічних потоків. Випущена дослідно-промислова партія модифікатора каталітичної системи процесу прямого хлорування етилену і проведені її дослідно-промислові випробовування. Показано, що застосування натрієвої солі перфторованої сульфокислоти дозволяє підвищити селективність утворення 1,2-дихлоретану з 98,9% до 99,3%, при цьому вміст трихлоретану спадає з 0.42% до 0.29%, тобто у 1,8 раз. Dissertation research is devoted to the solving of the actual scientific and practical problem: increase of selectivity of process of liquid-phase direct chlorination of ethylene to 1,2-dichloroethane by modification of the industrial catalyst on the basis of ferric chlorides and sodium salt of perforated sulfonic acid. By analyzing the stages of production of 1,2-dichloroethane, it was determined that the main factor influencing the selectivity of the process is the ratio of the components of the catalytic system, as well as its instability under the conditions of the reaction. It is established that the most effective method of stabilizing the catalytic system is the introduction of modifiers of different nature. It is these modifiers that affect the operation of the catalyst, so their search is aimed at dissertation research. The mechanism of the reaction of direct chlorination of ethylene is specified and it is shown that the reaction rate depends on the concentration of catalyst and promoter and their complex compound [NaFeСІ4], as well as the transition complex with ethylene [Na [Fe [С2Н4Cl) 4]), and takes place in the diffusion zone, providing the possibility of formation of complex compounds between the catalyst, promoter and ethylene by a new reaction mechanism. It is shown that the use of ammonium chloride (electron-donor compound) as stabilizers of the catalytic complex does not give a positive effect, and the sodium salt of perfluorinated sulfonic acid (electron-acceptor compound) leads not only to an increase in the content of sodium ions in the catalytic system and to -achieving their design values, but also to increase the purity of 1,2-dichloroethane and reduce the content of by-products, while the dispersion of the catalytic system is of secondary importance. It is established that the modifier not only stabilizes the catalytic complex, but allows to reduce its preparation time by half. The optimal stabilizer concentration is determined.The composition of the sludge that clogs the gas pipeline from the furnace to the steam generator of the heat utilization system during thermal neutralization of vat residues of vinyl chloride production has been determined. The principles of technology of extraction of iron chloride - catalyst of direct chlorination of ethylene - from technological streams are offered and it is shown that extraction of iron compounds should be carried out with technical water at elevated (about 350K) temperature, and also methods of utilization of organochlorine waste of vinyl chloride production. A basic technological scheme for the extraction of iron-containing catalyst and ways to solve technological problems that arise during the combustion of organochlorine residues in the production of vinyl chloride have been developed. An experimental-industrial batch of a modifier of the catalytic system of the process of direct chlorination of ethylene was released and its experimental-industrial tests were carried out. It is shown that the use of sodium salt of perfluorinated sulfonic acid can increase the selectivity of the formation of 1,2-dichloroethane from 98.9% to 99.3%, while the content of trichloroethane decreases from 0.42% to 0.29%, ie 1.8 times. Two licenses of Inter-Synthesis LLC, Boryslav, for the production of a catalytic system stabilizer and KARPATNAFTOKHIM LLC for its use in the process of direct chlorination of ethylene were sold. The actual economic effect achieved during the tests amounted to 88,000 UAH. The expected economic effect from the implementation is about 1 million UAH per year. В диссертационном исследовании разрешена актуальная научнопрактическая задача: повышение селективности процесса жидкофазного прямого хлорирования этилена до 1,2-дихлорэтана путем модификации промышленного катализатора на основе хлоридов железа и натрия натриевой солью перфторированной сульфокислоты. Уточнен механизм реакции прямого хлорирования этилена и показано, что скорость реакции зависит от концентрации катализатора и промотора и их комлексного соединения [NаFeСІ4], а также переходного комплекса с этиленом [Na[Fe(С2Н4Cl)4] и протекает в диффузионной области, что предусматривает образование комплексных соединений между катализатором, промотором и этиленом за новым механизмом. Показано, что использование в качестве стабилизатора каталитического комплекса хлорида аммония не дает положительного эффекта, а натриевая соль перфторированной кислоты благоприятствует не только увеличению содержания ионов натрия в каталитической системе , чистоты дихлорэтана но и уменьшению содержания побочных продуктов, при этом степень дисперсности каталитической системы имеет второстепенное значение. Установлено, что модификатор не только стабилизирует каталитический комплекс, но и сокращает время его приготовления в два раза. Определена оптимальная концентрация модификатора. Определен состав шлама, загрязняющего газопровод от печи до парогенератора системы утилизации тепла при переработке кубовых остатков производства дихлорэтана. Предложены принципы технологии извлечения хлорида железа – катализатора прямого хлорирования этилена – из технологических потоков. Выпущена опытно-промышленная партия модификатора каталитической системы процесса прямого хлорирования этилена и проведены ее опытнопромышленные испытания. Показано, что использование натриевой соли перфторированной сульфокислоты позволяет увеличить селективность образования 1,2-дихлорэтана с 98,9% до 99,3%, при этом содержание трихлорэтана снижается с 0.42% до 0.29%, т.е.у 1,8 раза.
Improvement of ethylene chlorination technology
Усовершенствование технологии хлорирования этилена
Keywords: хлорування; етилен; 1,2-дихлоретан; трихлоретан; каталізатор; модифікатор; селективність; chlorination; ethylene; 1,2-dichloroethane; trichloroethane; catalyst; modifier; selectivity; хлорирование; этилен; 1,2-дихлорэтан; трихлорэтан; катализатор; модификатор; селективность; 547.412.23.07; 541.128.1. 661.723.2